Pandangan Etika Kristen Terhadap Perkawinan - Aren Kristin; Azarya Aprinata; Natalia Natalia; Sarmauli Sarmauli (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Marriage is a sacred relationship established by the Lord God. Marriage in Christianity reflects an eternal covenant through promises to God that humans should maintain so that both parties understand that marriage is part of God's plan for human life. The aim of this research is to identify the nature of marriage in Christianity, describe the concept of marriage in Christian teachings, explain the relationship between Christian ethics and marriage. Data collection techniques through literature study from various sources in the form of books and journals. Christian ethics emphasizes the importance of maintaining purity in marriage according to God's commandments stated in Malachi 2: 15-16. In this context, marriage is seen as a sacred bond that cannot be broken by humans, and Christians are obliged to avoid adultery and divorce.